Queen-queen competition by precocious male production in multiqueen ant colonies - Yamauchi, Katsusuke; Ishida, Yasuko; Hashim, Rosli; Heinze, Jürgen (Elsevier, 2006)
Arriving earlier in the breeding area than his rivals may be beneficial for a male when females mate only once or during a short time span. The timing of a male's entrance is usually determined by the male himself, e.g., through returning early from his winter quarters or through accelerated larval development [1-3]. Here, we document a surprisingly simple way of "first come, first served" in a species with local mate competition. In multiqueen colonies of a Cardiocondyla ant, mother queens make sure that their own sons are the first to monopolize mating with a large harem of female sexuals by producing extremely long-lived males early in colony life. Whereas queens in newly founded single-queen colonies started to produce male and female sexuals only several weeks after the eclosion of their first worker off spring, queens in multiqueen colonies precociously reared sons long before the first female sexuals and even before the emergence of their first workers. These early males killed all later emerging males in the nest and mated with all female sexuals subsequently produced. Our data document that the patterns of growth and productivity of insect colonies are surprisingly flexible and can be turned upside down under appropriate selection pressures.